Perilaku Konsumen Gen Y dan Gen Z Dalam Pengambilan Keputusan Pembelian : Studi Komparatif Japanese Food dan American Food - Eri Yanti Nasution; Efry Kurnia (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2021)
This study aims to examine differences in consumer behavior of generation Y and generation Z in food purchasing decisions of Japanesse food and American food. Sampling using a stratified random sampling method of 100 consumers of Japanesse food and American food in the city of Medan. The data collection method was by distributing online questionnaires to 50 Y generation respondents and 50 generation Z questionnaires. Data analysis methods in this study were T test and factor analysis test. The results of the beza T test explain that there are differences in behavior between generation Y and generation Z in decision making. The factors that influence these differences are personal and social factors that are generated based on the factor analysis test.